Clinical and morphological parallels in conditions of impaired platelet-vascular hemostasis in patients with type 2 diabetes. - Pertseva, N. O.; Turlyun, T. S. (Морфологія / Morphologia / Morfologìâ, 2011)
Current experimental and clinical data was analyzed to evaluate the ultrastructural changes of platelets and their interaction with other cells in conditions of impaired hemostasis during the type 2 diabetes development and following complications. Special attention was paid to determine the correlations between the revealed morphological changes of platelets and the functional and clinical data. We show that ultrastructural studies to reveal the morphological signs of platelets abilities to activate, as well as studies of their structural and functional changes in the conditions of hyperglycemia, and the features of their interaction with the blood cells and endothelial cells are among the most important questions in the field. Addressing these issues will contribute to the understanding of the important mechanisms of pathogenesis, as well as to explain the cascade of clinically relevant lesions, which not only complicate the course of the disease, but also determine its outcome.